Journal of Preventive Medicine and Hygiene 2021
DOI: 10.15167/2421-4248/jpmh2021.62.3.1663
|View full text |Cite
|
Sign up to set email alerts
|

University community-based survey on the knowledge, attitude and perception about COVID-19 pandemic: the Federal University of Agriculture, Abeokuta, Nigeria as a case study

Abstract: Summary Introduction Coronavirus disease (COVID-19) is impacting social, economic and political patterns globally. To contain its spread, Nigeria like many other countries, imposed drastic measures such as lockdown/curfew. Objectives This study assessed the knowledge, attitude and perception (KAP) about COVID-19 pandemic among members of staff of a university community in Nigeria. University staff members contribute to national development through dissemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
0
1
Order By: Relevance
“…The findings are similar to a study conducted in Nigeria among adult residents during the ease of the lockdown, which also reported that a very large proportion (98.8%) of the respondents had a good knowledge of the disease. However, when compared to other published studies carried out in the early stages of the pandemic and before the ease of the restrictions [ 25 - 27 ] we found that the knowledge levels were significantly improved post lockdown. The internet/social media was also the main source of information for this group.…”
Section: Discussioncontrasting
confidence: 75%
“…The findings are similar to a study conducted in Nigeria among adult residents during the ease of the lockdown, which also reported that a very large proportion (98.8%) of the respondents had a good knowledge of the disease. However, when compared to other published studies carried out in the early stages of the pandemic and before the ease of the restrictions [ 25 - 27 ] we found that the knowledge levels were significantly improved post lockdown. The internet/social media was also the main source of information for this group.…”
Section: Discussioncontrasting
confidence: 75%